Например есть вот что (7/√2 +3)+(14/4+√2) Как максимально упростить это выражение?

Например есть вот что (7/√2 +3)+(14/4+√2) Как максимально упростить это выражение?
Гость
Ответ(ы) на вопрос:
Гость
[latex] \frac{7( \sqrt{2}-3) }{( \sqrt{2}+3)( \sqrt{2}-3)} + \frac{14( 4-\sqrt{2}) }{( 4+\sqrt{2})( 4-\sqrt{2})} = \\ \\ = \frac{7( \sqrt{2}-3) }{( \sqrt{2})^2-3^2} + \frac{14( 4-\sqrt{2}) }{ 4^2-(\sqrt{2})^2} = \\ \\ \frac{7( \sqrt{2}-3) }{2-3} + \frac{14( 4-\sqrt{2}) }{ 16-2} = \\ \\ \frac{7( \sqrt{2}-3) }{-1} + \frac{14( 4-\sqrt{2}) }{ 14} = \\ \\ -7 \sqrt{2}+21+4- \sqrt{2}=25-8 \sqrt{2} [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы